FAMILIARITY EXPERIENCE AND PREFERENCE FOR SIDDHA TREATMENT (Journal of Pharmaceutical Negative Results, 2023)
Siddha medicine is a traditional system of healing that originated in South India and is regarded to be one of India's oldest medical systems. Siddha System of Medicine played an important role in the health care scenario of the people in Tamil Nadu. The government sector contributes significantly to the development of the system throughout the country and still the number of users is less. The objective of this study is to understand the demographic profile of the respondents, the awareness and preference for siddha treatment in Kancheepuram district of Tamil Nadu. Data were collected from 252 respondents and the results show the lack of knowledge about the treatment available for various ailments in siddha.